2018
DOI: 10.1080/15384047.2018.1470724
|View full text |Cite
|
Sign up to set email alerts
|

Molecular alterations associated with chronic exposure to cigarette smoke and chewing tobacco in normal oral keratinocytes

Abstract: Tobacco usage is a known risk factor associated with development of oral cancer. It is mainly consumed in two different forms (smoking and chewing) that vary in their composition and methods of intake. Despite being the leading cause of oral cancer, molecular alterations induced by tobacco are poorly understood. We therefore sought to investigate the adverse effects of cigarette smoke/chewing tobacco exposure in oral keratinocytes (OKF6/TERT1). OKF6/TERT1 cells acquired oncogenic phenotype after treating with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 81 publications
(79 reference statements)
0
18
0
1
Order By: Relevance
“…30 We have previously observed marked overexpression and activation of MAPK1 in OKF6/ TERT1 cells chronically exposed to cigarette smoke. 12 Despite distinct genomic anomalies in OKF6/TERT1 cells chronically treated with cigarette smoke and shisha extract, interferon-signaling cascade was a commonly affected pathway in both models.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…30 We have previously observed marked overexpression and activation of MAPK1 in OKF6/ TERT1 cells chronically exposed to cigarette smoke. 12 Despite distinct genomic anomalies in OKF6/TERT1 cells chronically treated with cigarette smoke and shisha extract, interferon-signaling cascade was a commonly affected pathway in both models.…”
Section: Discussionmentioning
confidence: 96%
“…Previous study by our group elucidated the molecular alterations in oral cells upon chronic cigarette smoke exposure. 12 In that study, OKF6/TERT1-Parental cells were chronically treated with cigarette C>T transversions is known to be associated with various cancers. 21 We did not observe any commonalities among genomic anomalies, however, pathway analysis using IPA predicted activation of mitogen-activated protein kinase 1 (MAPK1) pathway (z-score ≥ 2) ( Figure 2B).…”
Section: Comparison Of Okf6/tert1-smoke and Okf6/tert1-shishamentioning
confidence: 99%
See 2 more Smart Citations
“…However, molecular alterations associated with cigarette smoke exposure in esophageal cells remains poorly understood. We and others have shown that in vitro cell models with chronic cigarette smoke extract/condensate are helpful in understanding oncogenic transformation of non-neoplastic esophageal cells (41), lung epithelial type-II cells (42), urothelial cells (43), breast epithelial cells (44), and oral cells (45,46). Cigarette smoke contains more than 70 carcinogenic compounds that are responsible for development of cancer.…”
Section: Discussionmentioning
confidence: 99%